2020
DOI: 10.1002/pssr.202000257
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Spin Correlated‐Plasmons Ranging from Infrared to Ultraviolet in Pr0.6Sr0.4Co1−xMnxO3

Abstract: Herein, new spin correlated‐plasmons in Pr0.6Sr0.4Co1−xMnxO3 (x = 0–0.4) that are tunable and stable at room temperature are demonstrated. Using advanced spectroscopic techniques, the charge, spin, and orbital interaction that triggers the spin correlated‐plasmons in spin‐polarized Co4+, O2−, and Mn4+ is identified. As a function of x, Co4+ systematically changes the spin state of the spin correlated‐plasmons (from high, intermediate, to low spin), which also sequentially transforms the metallic cobaltite into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The multifrequency characteristic of LSNO enhances the optical modulation flexibility, adapting to diverse wavelength ranges. Aligned with correlated plasmons observed in copper oxide-based high-temperature superconductors, , LNO exhibits a unique feature: simultaneous excitation of conventional and correlated plasmons in the same position of LF spectraan unprecedented phenomenon. This supports the efficient coupling of correlated plasmons to free-space photons, enhancing metallic plasmon excitation.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The multifrequency characteristic of LSNO enhances the optical modulation flexibility, adapting to diverse wavelength ranges. Aligned with correlated plasmons observed in copper oxide-based high-temperature superconductors, , LNO exhibits a unique feature: simultaneous excitation of conventional and correlated plasmons in the same position of LF spectraan unprecedented phenomenon. This supports the efficient coupling of correlated plasmons to free-space photons, enhancing metallic plasmon excitation.…”
Section: Resultsmentioning
confidence: 94%
“…Previous studies have shown that the existence of both peaks in ε 2 and LF spectra suggests a strong coupling between the optical and plasmonic excitations of LNO and is indicative of correlated plasmons. 8,41 This implies that peak B* is the correlated plasmon excitation peak in LNO. Similarly, in LSNO (0.25), peak B* (∼3.34 eV) and peak B′ (∼3.36 eV) were observed in the same position in the ε 2 spectrum and LF spectrum, suggesting the presence of correlated plasmons as well.…”
Section: Conventional and Correlated Plasmons Of Lsno Epitaxialmentioning
confidence: 94%
“…This has prompted recent experimental studies to find correlated plasmons in novel materials systems like Mott-insulating cuprates [26] and topological insulators [27,28]. Other experimental work has also focused on finding other plasmons arising from the interplay of short-range and long-range interactions in materials, like quasilocal plasmons [29,30] and spincorrelated plasmons [31,32].…”
Section: Introductionmentioning
confidence: 99%